Coins of the State of the Teutonic Order in Prussia in the Territory of Medieval Ukraine and Neighboring Lands: The Contemporary Scholarly Discourse - Shataylo, Mykola (Revista Arheologică, 2026)
The article examines the distribution and historiography of coins of the Teutonic Order’s state in Prussia within the monetary circulation of Eastern Europe, with particular attention to the Ukrainian, Belarusian, and Moldavian lands of the late Middle Ages. It has been established that the spread of Teutonic coinage exhibited a clearly defined regional differentiation, determined by the intensity of economic, political, and military contacts with the Order’s state. While in the border regions of the Kingdom of Poland these coins could play a significant role in monetary circulation, in the lands of the Grand Duchy of Lithuania they functioned as a secondary element of a multi-currency system, whereas in the Principality of Moldavia their presence was episodic. The article outlines the main directions in the development of historiography on this issue. Two interrelated levels of research are identified: the first, in which Teutonic coins are considered within broader archaeological, topographical, and regional numismatic studies; and the second, represented by specialized works in which this material is treated as an independent subject of analysis. Within the latter, key research problems are defined, including the topography of finds, the relationship between single finds and hoards, issues of attribution, the problem of counterfeiting, and the use of numismatic materials for reconstructing economic connections. The historiographical analysis demonstrates that, despite the growing number of studies, Teutonic Order coinage has only relatively recently emerged as a distinct object of research. For a long time, it remained embedded within broader numismatic syntheses, which resulted in the fragmentary character of its study. Additional difficulties arise from terminological ambiguity and varying levels of source attribution. As a result, the current state of research is characterized by uneven development and requires further systematization of material and the development of coherent methodological approaches.
Keywords: historiography; numismatics; coin; numismatic sources; methodology; monetary circulation; die analysis; topographyof coin finds; Middle Ages; Teutonic Order; scholarly discourse; coin hoard